2021
DOI: 10.3389/fcell.2021.703966
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Identity of GLP-1R, GLP-2R, and GIPR Expressing Cells and Signaling Circuits Within the Gastrointestinal Tract

Abstract: Enteroendocrine cells directly integrate signals of nutrient content within the gut lumen with distant hormonal responses and nutrient disposal via the production and secretion of peptides, including glucose-dependent insulinotropic polypeptide (GIP), glucagon-like peptide 1 (GLP-1) and glucagon-like peptide 2 (GLP-2). Given their direct and indirect control of post-prandial nutrient uptake and demonstrated translational relevance for the treatment of type 2 diabetes, malabsorption and cardiometabolic disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 184 publications
0
5
0
Order By: Relevance
“…GLP-1 binds to the GLP-1R, a G-protein–coupled receptor widely expressed in the pancreas, gastrointestinal tracts, kidneys, lungs, and hearts [ 79 ]. Glp-1R mRNA expression is the highest in the epithelial fraction of the jejunum, followed by the ileum and colon [ 80 ]. Recently, He and collaborators reported that gut intraepithelial T cells regulate GLP-1 bioavailability by capturing GLP-1 on GLP-1Rs and impacting L cell numbers [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 binds to the GLP-1R, a G-protein–coupled receptor widely expressed in the pancreas, gastrointestinal tracts, kidneys, lungs, and hearts [ 79 ]. Glp-1R mRNA expression is the highest in the epithelial fraction of the jejunum, followed by the ileum and colon [ 80 ]. Recently, He and collaborators reported that gut intraepithelial T cells regulate GLP-1 bioavailability by capturing GLP-1 on GLP-1Rs and impacting L cell numbers [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, in GLP-1R knockout mice, RYGB still exhibited improved glucose homeostasis (9,14), and a GLP-1R antagonist did not deteriorate glucose homeostasis in patients who achieved diabetes remission following RYGB (5). Our previous study (15) involving ileal transposition performed on Goto-Kakizaki (GK) rats showed rapid improvement of glucose tolerance and a delayed improvement of insulin resistance, accompanied with a decreased insulin level instead of the increased insulin secretion subsequently induced by increased GLP-1 expression (16,17), suggesting that it might have been glucose tolerance improvement rather than increased GLP-1 expression that led to the improvement of insulin resistance. Taken together, the EIA hypothesis cannot fully explain diabetic improvement in MBS, and further studies are required to define the role of GLP-1 in glucose metabolism (18).…”
Section: Introductionmentioning
confidence: 95%
“…GLP-2 effects are mediated by its interaction with a specific receptor (GLP-2R), a G protein-coupled receptor expressed in both humans and animals at either the central or the peripheral level [1,6,7], including the gastrointestinal tract [8][9][10]. In the latter, GLP-2R expression occurs in enteroendocrine and subepithelial cells, myofibroblasts and in myenteric neurons [11].…”
Section: Introductionmentioning
confidence: 99%